Triboelectric generator for wearable devices fabricated using a casting method. Issue 12 (26th January 2016) - Lee, Chang Jun; Choi, A. Young; Choi, Changsoon; Sim, Hyeon Jun; Kim, Seon Jeong; Kim, Youn Tae
Abstract : We fabricate an efficient triboelectric generator (TEG) using inexpensive materials that are readily available in our surroundings. By casting PDMS, we perform micropatterning on the surface of sandpaper. Abstract : In this study, we fabricate an efficient triboelectric generator (TEG) using inexpensive materials that are readily available in our surroundings. By casting polydimethylsiloxane (PDMS), we perform micropatterning on the surface of sandpaper. We use aluminum foil as an electrode and electrified body. To improve the durability and resilience of the aluminum foil, we use a polyethylene terephthalate (PET) film. PET/Al electrodes may act on the bottom and top performing the role of an electrode, and at the same time as an electrified body. We applied an external force of 1 N using the pushing tester on the TEG created using the PDMS, and we then connected an external resistor to confirm the output power. Based on the patterning TEG, we confirmed that there was an increase in the output voltage by a factor of about 10 compared to the flat TEG's output voltage of 15 V. We turned on 79 LEDs by hand pushing, and produced an output voltage of more than 250 V. In addition, we turned on 39 LEDs by performing a bending test with an average output voltage of more than 100 V.